Ventricular scar channel entrances identified by new wideband cardiac magnetic resonance sequence to guide ventricular tachycardia ablation in patients with cardiac defibrillators. Issue 4 (26th February 2020) - Roca-Luque, Ivo; Van Breukelen, Ana; Alarcon, Francisco; Garre, Paz; Tolosana, Jose M; Borras, Roger; Sanchez, Paula; Zaraket, Fatima; Doltra, Adelina; Ortiz-Perez, Jose T; Prat-Gonzalez, Susanna; Perea, Rosario J; et al.
Abstract: Aims: Ventricular tachycardia (VT) substrate-based ablation has become a standard procedure. Electroanatomical mapping (EAM) detects scar tissue heterogeneity and define conduction channels (CCs) that are the ablation target. Late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) is able to depict CCs and increase ablation success. Most patients undergoing VT ablation have an implantable cardioverter-defibrillator (ICD) that can cause image artefacts in LGE-CMR. Recently wideband (WB) LGE-CMR sequence has demonstrated to decrease these artefacts. The aim of this study is to analyse accuracy of WB-LGE-CMR in identifying the CC entrances. Methods and results: Thirteen consecutive ICD-patients who underwent VT ablation after WB-LGE-CMR were included. Number and location of CC entrances in three-dimensional EAM and in WB-LGE-CMR reconstruction were compared. Concordance was compared with a historical cohort matched by cardiomyopathy, scar location, and age (26 patients) with LGE-CMR prior to ICD and VT ablation. In WB-CMR group, 101 and 93 CC entrances were identified in EAM and WB-LGE-CMR, respectively. In historical cohort, 179 CC entrances were identified in both EAM and LGE-CMR. The EAM/CMR concordance was 85.1% and 92.2% in the WB and historical group, respectively ( P = 0.66). There were no differences in false-positive rate (CC entrances detected in CMR and absent in EAM: 7.5% vs 7.8% in WB vs. conventional CMR, P = 0.92) nor in false-negative rate (CC entrances present in EAM not detected in CMR: 14.9% vs.7.8% in WB vs. conventional CMR, P = 0.23). Epicardial CCs was predictor of poor CMR/EAM concordance (OR 2.15, P = 0.031). Conclusion: Use of WB-LGE-CMR sequence in ICD-patients allows adequate VT substrate characterization to guide VT ablation with similar accuracy than conventional LGE-CMR in patients without an ICD.